KR-31466, a Benzopyranylindol Analog, Attenuates Hypoxic Injury Through Mitochondrial KATP Channel and Protein Kinase C Activation in Heart-Derived H9c2 Cells - Yi-Sook Jung; Yoon Seok Jung; Mi-Young Kim; Min Hwa Kim; Sunkyung Lee; Kyu Yang Yi; Sung Eun Yoo; Soo Hwan Lee; Eun Joo Baik; Chang-Hyun Moon; Joon Pil Cho (Elsevier, 2003)
In the present study, we investigated whether a novel benzopyranylindol analogue, KR-31466 (KR466) (1-[(2S,3R,4S)-3,4-dihydro-2-dimethoxymethyl-3-hydroxy-2-methyl-6-nitro-2H-1-benzopyran-4-yl]-1H-indole-2-carboxylic acid ethyl ester) can attenuate hypoxic injury in heart-derived H9c2 cells and, if so, whether the protective effect of KR466 is mediated through mitochondrial ATP-sensitive potassium (mtKATP) opening. The treatment of H9c2 cells with KR466 (3 - 30 μM) significantly reduced hypoxia-induced cell death in a concentration-dependent manner, as shown by lactate dehydrogenase release and propidium iodide-uptake. In addition, KR466 (10 μM) significantly reduced the increase in hypoxia-induced TUNEL-positive cells, suggesting its anti-apoptotic potential in H9c2 cells. The protective effects of KR466 were abolished by 5-hydroxydecanoate, a specific blocker of the mtKATP channel, suggesting the involvement of the mtKATP channel in the protective effect of KR466. A specific inhibitor of protein kinase C (PKC), chelerythrine (3 μM), significantly attenuated the protective effect of KR466 against hypoxia-induced cardiac cell death. In conclusion, our results suggest that KR466 can protect H9c2 cells from hypoxia-induced death through mtKATP channel opening and PKC activation.